2014
DOI: 10.1016/j.cmet.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Congenital Hyperinsulinism Cause DNA Double-Strand Breaks and p53 Activity in β Cells

Abstract: β cell failure in type 2 diabetes (T2D) is associated with hyperglycemia, but the mechanisms are not fully understood. Congenital hyperinsulinism caused by glucokinase mutations (GCK-CHI) is associated with β cell replication and apoptosis. Here, we show that genetic activation of β cell glucokinase, initially triggering replication, causes apoptosis associated with DNA double-strand breaks and activation of the tumor suppressor p53. ATP-sensitive potassium channels (KATP channels) and calcineurin mediate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 60 publications
(85 reference statements)
10
134
1
2
Order By: Relevance
“…In the context of hIAPP toxicity in hTG mice, the Nrf2 pathway was suppressed by calpastatin in hTG:hCAST mice, implying that hIAPP-induced oxidative stress is overcome by suppression of calpain hyperactivation ( Figure 5A). These data were consistent with the presence of increased β cell DNA damage detected by histone H2AX phosphorylation (P-H2AX), a marker of double-strand break repair (37), in hTG mice compared with WT controls (0.94% ± 0.18% vs. 0.31% ± 0.05%, P < 0.001; Figure 5B). Calpastatin-mediated suppression of calpain hyperactivation suppressed the hIAPP-induced DNA damage (0.22% ± 0.06%, P < 0.001 vs. hTG; Figure 5, B and C), further supporting the importance of calpain hyperactivation in oxidative stress.…”
Section: Hiapp-induced Calpain Hyperactivation Is Accompanied By Calpsupporting
confidence: 76%
See 1 more Smart Citation
“…In the context of hIAPP toxicity in hTG mice, the Nrf2 pathway was suppressed by calpastatin in hTG:hCAST mice, implying that hIAPP-induced oxidative stress is overcome by suppression of calpain hyperactivation ( Figure 5A). These data were consistent with the presence of increased β cell DNA damage detected by histone H2AX phosphorylation (P-H2AX), a marker of double-strand break repair (37), in hTG mice compared with WT controls (0.94% ± 0.18% vs. 0.31% ± 0.05%, P < 0.001; Figure 5B). Calpastatin-mediated suppression of calpain hyperactivation suppressed the hIAPP-induced DNA damage (0.22% ± 0.06%, P < 0.001 vs. hTG; Figure 5, B and C), further supporting the importance of calpain hyperactivation in oxidative stress.…”
Section: Hiapp-induced Calpain Hyperactivation Is Accompanied By Calpsupporting
confidence: 76%
“…Mitochondrial network disruption and dysfunction with increased ROS generation and DNA damage are prominent in protein misfolding diseases and are characteristic of β cells in both humans with T2D and hIAPP transgenic models of T2D (27,37). This disruption might be mediated directly by the membrane-permeable toxic oligomers, by hyperactivated calpains (45,46), and by Ca 2+ overload as a result of dysregulated ER Ca 2+ leakage (47), particularly if the latter were to occur at the mitochondrial endoplasmic reticulum membrane interface.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In addition, a recent study demonstrated that a gain of function mutation of glucokinase results in increased b-cell proliferation that corresponds with increased apoptosis rates. 26 To determine the effect of AURKA overexpression on b-cell apoptosis rates, we measured the percentage of phosphorylated histone gH2AX positive primary rat islet b-cells. Phosphorylated histone gH2AX staining is an indicator of DNA double-strand breaks that are observed during apoptosis.…”
Section: Aurka Does Not Increase Apoptosis Rates In Primary Rat B-cellsmentioning
confidence: 99%
“…Glucose metabolism is required for β cell proliferation, as lack of glucokinase, a key enzyme in glycolysis that converts glucose to glucose-6-phosphate, decreases β cell proliferation whereas treatment with a small-molecule glucokinase activator stimulates β cell proliferation (104). However, the pro-proliferative effect of glucose is only observed in the short term, while sustained exposure of β cells to high glucose can cause glucotoxicity, resulting in DNA damage and apoptosis, as also seen in β cells from T2D patients (105). Therefore, there is a need to better understand where the mitogenic and DNA damage pathways diverge before the glucose-induced mitogenic pathway can be considered for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 98%